Surgical Site Infection after Cesarean Delivery in Times of COVID-19 - Antonello, Vicente Sperb; Dallé, Jessica; Antonello, Ivan Carlos Ferreira; Benzano, Daniela; Ramos, Mauro Cunha (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To analyze effects of the COVID-19 pandemic on the consumption of personal protective equipment and products (PPEP), as well as the frequency of surgical site infection (SSI) among non-COVID-19 patients submitted to cesarean sections.Methods A retrospective study was conducted in a maternity unity of a public teaching hospital which was not part of the reference service for COVID-19 treatment. It compared PPEP consumption and the occurrence of SSI after cesarean sections in monthly periods before and after the occurrence of the first case of COVID-19 in Porto Alegre, state of Rio Grande do Sul, Brazil. Personal protective equipment and products consumption was measured as units of masks, gloves, gowns, and caps, and use of alcohol-based products or soap for hand sanitation as ml/patient/day. The SSI index was calculated as the proportion of cases of SSI over the number of cesarean sections performed monthly during the study period.Results There was an increase in all measured items of PPEP, with consumption of disposable masks with a median of 1,450 units in the pre-COVID period, and of 2550 in the post-COVID period (a 75.9% increase). A decrease of 49% in SSI was detected, with a median of 1.74 in the pre-COVID period and of 0.89 in the post-COVID period.Conclusion The increase in consumption of PPEP could be a result of safer practices adopted by healthcare workers with the advent of COVID-19, of which the following reduction in the occurrence of SSI could be a direct consequence. Despite the severity of the crisis, one could state that extreme situations can lead to valuable reflections and opportunities for improvement.
Keywords: surgical wound infection; cesarean section; personal protective equipment; coronavirus